DIGITAL TECHNOLOGIES IN CREATING CHOREOGRAPHIC PERFORMANCES - Volchukova, Viktoriia; Tishchenko, Olena; Barabash, Olha; Nos , Oleksandr (The Modern Higher Education Review, 2024)
Digital technologies such as computers, websites, 3D modelling and VR reality, multimedia, computer graphics are increasingly used by contemporary choreographers to create performances, choreographic shows and contemporary choreographic works. Nowadays, not every viewer can understand digital media as a new way of perceiving choreographic art. The viewer also underestimates the objects of media art, i.e. the technologies that are used to create a choreographic work. The fact that computer technologies were used in the process of their creation, levels the artistic intention of the choreographer and devalues his creative process. Thus, contemporary dance performances that use sensors to control stage and sound design cannot be understood by everyone and perceived as new media art. Digital technologies are not perceived as a representation of an audio or multimedia object. Like contemporary dance itself, it is the creation of an imaginary world by the dancer's body. All this is based on certain symbols, because choreographic art is symbolic by nature. As a result, contemporary dance creates a new system of movements and positions of the body in space, which is still developing very rapidly, and which increases the perception of contemporary compositions due to the use of media technologies by contemporary choreographers. The article is addressed to choreographers, choreography teachers, teachers of dance disciplines and directors of dance companies who should be prepared to create highly artistic choreographic performances, dance show projects, performances using modern digital technologies and have a methodology for staging such art products.